Competency categorization and roles of online teachers from the perspective of university students - Tawafak, Ragad M.; Al-Obaydi, Liqaa Habeb; Pikhart, Marcel (Frontiers in Psychology, 2023)
The teaching and learning process is facing many unprecedented challenges that require innovative solutions in the short life of knowledge and the abrupt development of technology. Some of these challenges are the new roles of teachers who are the main constituents in the online teaching process. The main aim of this study revolved around determining and analyzing university students' priorities concerning the competency categorization and roles of online teachers. The research was based on Moodle and Google classroom to validate the competency elements with the final aim of improving teaching and learning processes. The data were collected by using an online questionnaire that evaluated eight dimensions of competencies and roles of online teachers. The research sample consisted of 430 participants (aged between 19 and 30) from Iraq and Oman. The results obtained from these two countries were very similar as the respondents highlighted professional, pedagogical and social competencies in their teachers. It further shows that though the applications used in the two contexts were different (Google classroom with Google Meet or Moodle), it didn’t affect the final results gained. The results of this survey could be important for further analysis of online teaching practice and bring several important insights regarding the possibilities of online teaching.